Determinants of Patient Loyalty in Healthcare: The Multifaceted Influence of Demographics and Nurses' Caring Behavior - Tita Rohita; Dedeng Nurkholik (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Patient loyalty is a crucial factor in providing quality healthcare services. One effective strategy to enhance healthcare service standards is improving the caring behavior of nurses. The success of nurses in delivering caring and empathetic care can significantly influence patient loyalty, making it an essential focus for healthcare providers. Objective: This study aims to explore the factors influencing patient loyalty within a healthcare context. Methods: A cross-sectional design was utilized in this study, involving 144 inpatients selected through purposive random sampling from private and government hospitals. Data were collected using questionnaires and analyzed using chi-square and ANOVA tests. Results: The analysis identified three factors significantly correlated with patient loyalty: Caring Behavior of Nurses: p < 0.0001, Education: p < 0.007, Marital Status: p < 0.001. The most influential factor was the caring behavior of nurses, with effect sizes indicating a strong relationship. In contrast, demographic factors such as age and gender did not show a significant correlation with patient loyalty. Conclusion: The findings highlight that the most significant determinant of patient loyalty is the caring behavior of nurses, followed by education and marital status. To enhance patient loyalty and overall healthcare quality, it is crucial to strengthen nurse training programs that focus on empathy and caring behaviors. Additionally, implementing services tailored to patients’ demographic characteristics can further improve loyalty. These insights can guide policymakers and practitioners in developing targeted training and healthcare policies that prioritize compassionate care, ultimately benefiting patient satisfaction and retention.